2020
DOI: 10.3390/agronomy11010065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plant Growth Regulators and N Rate on the Morphological Traits of Generative Tillers and Seed Yields of Chewings and Strong Creeping Red Fescue

Abstract: Plant growth regulators (PGRs) are used as a management tool to minimize plant height and subsequent stem lodging in grass seed crops. Their efficacy is influenced not only by the method of application, but also by the management and genetic variations within and between species. This aim of the study was to evaluate the effect of PGRs on morphological traits of generative tillers and seed yield of Festuca rubra L ssp. rubra (strong creeping red fescue) and F. r. L ssp. commutata (Chewings red fescue) under lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In addition to a higher application rate, a combination of trinexapac ethyl with chlormequat chloride could also lead to an increase in seed yield. Studies by Szczepanek et al (2021) showed a clear effect in creeping red fescue ( Festuca rubra ) seed propagations, but more research is needed to confirm the effect in orchardgrass seed propagation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a higher application rate, a combination of trinexapac ethyl with chlormequat chloride could also lead to an increase in seed yield. Studies by Szczepanek et al (2021) showed a clear effect in creeping red fescue ( Festuca rubra ) seed propagations, but more research is needed to confirm the effect in orchardgrass seed propagation.…”
Section: Discussionmentioning
confidence: 99%